M Marketing - Grewal, Dhruv; Levy, Michael 1950- (New York, NY McGraw-Hill Education, 2021)
"Throughout this edition numerous examples of how students engage in marketing activities every day of their lives-either as consumers or sellers of a product or service. In addition to providing the traditional study and reinforcement tools of most principles of marketing products, we also offer ways to help students think critically about and apply core concepts"--Provided by publisher.
Section one: Assessing the Marketplace -- Section two: Understanding the Marketplace -- Section three: Targeting the Marketplace -- Section four: Value Creation -- Section five: Value Capture -- Section six: Value Delivery: Designing the Channel and Supply Chain -- Section seven: Value Communication.
International student edition.
Includes bibliographical references and indexes.
Keywords: Marketing